Cecal Intussusception Diagnosed by Total Colonoscopy in a Child: A Case Report - Kakiuchi, Toshihiko; Esaki, Motohiro; Nakayama, Aiko; Ichinose, Fumio; Matsuo, Muneaki (Frontiers in Pediatrics, 2020)
Background: Ileocolic intussusception is the most common form of intussusception in children. Intussusception in the appendix or cecum without a lead point in a child is very rare and was found with total colonoscopy (TCS) and computed tomography. Case Presentation: A 9-year-old boy was admitted to our hospital with fever, vomiting, and two episodes of bloody diarrhea. Inflammatory bowel disease was suspected; TCS was performed and revealed intussusception whose advanced region was in the cecum. The diagnosis was idiopathic cecum intussusception. This case was unusual in that intussusception had occurred at a young age but without lead point; in addition, the intussusception had also occurred at the tip of the cecum. The intussusception was safely reduced by endoscopic procedures, and after improvement in the vomiting, the patient was safely discharged and has had no bloody stools since. Conclusion: We demonstrated cecal intussusception without lead point observed on TCS in a child.